Предмет: Алгебра,
автор: ilnarbaygildin
(х-1)(х^2+6х+9)=х^2+12+27 Помогите пж) распишите
Ответы
Автор ответа:
0
D=b^2-4ac,D=12^2-4*1*27=144-108=36,D>0.
x1,2=(-b+корень из D)2а.
x1=(-12- корень из 36)2*1=-9
x2=(-12+корень из 36)2а=-3
Следовательно х1=-9,а х2=-3.
Удачи!!!
x1,2=(-b+корень из D)2а.
x1=(-12- корень из 36)2*1=-9
x2=(-12+корень из 36)2а=-3
Следовательно х1=-9,а х2=-3.
Удачи!!!
Похожие вопросы
Предмет: Литература,
автор: maxim110829
Предмет: Музыка,
автор: shindyapinak
Предмет: Русский язык,
автор: kat30ivan
Предмет: Литература,
автор: Kabardinka
Предмет: Математика,
автор: marynanikitina